Cultural anthropology and disciplinary knowledge: a laboratory experience - Falcinelli, Floriana; Falteri, Paola; Pascolini, Francesca (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2017)
This article presents some experimental results of two didactic experiences that were conducted in the University of Perugia in the year 2014/2015: an experience has involved university teachers, tutor of trainees, tutors, school leaders, on a path of training conjunct in which we have been adopted strategies to promote participation and comparison, using as a source of learning the trainees' writing ('board diaries') and others materials. The experience was elaborated on starting with cultural anthropology, whose teaching is imparted into the course of study. Many groups of teachers have drawn to the anthropological approach for the critical reflections on Western thought in order to open it to the understanding of diversity; the anthropological approach has the liminal vocation , that puts it for its own tradition at border with other approaches, capable of dialogue with the various disciplinary knowledge